DESIGN THINKING MODELS IN DESIGN RESEARCH AND EDUCATION - Irbīte, Andra; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Design thinking has become a paradigm that is considered to be useful in solving many problems in different areas: both in development of design projects and outside of traditional design practice. It raises the question - is design thinking understood as a universal methodology in all cases? How it is interpreted in design education? The analysis of theoretical and design related literature indicates different basic and contextual challenges facing design today: increasing scale of social, economic and industrial borders; complexity of environment and systems; requirements in all levels. As specialists and researchers in the field of design have concluded, here are multiple disconnects betweenwhat the graduate design schools are teaching at the level of methods and what skills is already needed. The problems have been found also in interdisciplinary cooperation and research. In the context of design thinking models and problem solving methods, the analysis shows that design education implementers in public higher education institutions in Latvia are ready for local and global challenges.